2019
DOI: 10.1101/569772
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of pterygium on the ocular surface and meibomian glands

Abstract: 2627 Purpose: To analyze how ocular surface parameters correlate to pterygium and investigate the 28 possible impact on tear film and meibomian glands. Methods: we investigated objective parameters 29 of the ocular surface such as conjunctival hyperemia, tear film stability and volume, meibomian gland 30 dysfunction, dry eye disease, corneal topography comparing healthy individuals and correlating with 31 the pterygium clinical presentation. Results: A total of 83 patients were included. Corneal 32 astigmatism… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
(7 reference statements)
1
5
0
Order By: Relevance
“…Hence, the mean tear production values were significantly higher among the control subjects. This was corroborated in several studies [14][15][16][17] where people with pterygium where found to have lower tear production values. This study showed complaints of tearing, itching, foreign body sensation and redness among the pterygium subjects.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Hence, the mean tear production values were significantly higher among the control subjects. This was corroborated in several studies [14][15][16][17] where people with pterygium where found to have lower tear production values. This study showed complaints of tearing, itching, foreign body sensation and redness among the pterygium subjects.…”
Section: Discussionsupporting
confidence: 82%
“…[14] Pterygium growth and development has also been shown to be associated with tear film instability. [15] Hence the aim of this study was to investigate the level of tear production among adults with pterygium.…”
Section: Introductionmentioning
confidence: 99%
“…Fen Y et al 22 found significantly higher OSDI score(14.2) in pterygium patients. Ning Li 23 found pterygium patients had a significantly elevated OSDI value relative to the controls (20.11 ± 4.27 and 12.00 ± 2.87, respectively; p <0.001).Huping Wu et al 21 found that the OSDI value was significantly higher in pterygium patients than that of volunteers, 20.05 and 12.00 respectively, ( P<0.001).…”
Section: Study Was Found To Have Greater Correlation With Outdoor Activitymentioning
confidence: 94%
“…Mean difference of Meibomian gland expression was 92.86 in pterygium group and 48.14 in comparison group and the differences were highly significant(P<.05) ,indicating that pterygium patients suffer from meibomian gland dysfunction more than normal persons. Fen Y et al 12 Huping Wu et al 21 AnaCláudia et al 22 Ning Li et al 23 found pre and post-surgery effect on meibomian gland dysfunction, it improved after excision of pterygium.…”
Section: Study Was Found To Have Greater Correlation With Outdoor Activitymentioning
confidence: 99%
“…Tear osmolarity is a function of tear secretion and tear evaporation [26]. Studies have shown that lower tear production can lead to higher tear osmolarity levels [27]. And there is an interconnection between hyperosmolarity and tear instability [28].…”
Section: Declarationsmentioning
confidence: 99%